CHALLENGES AND SOLUTIONS IN TEACHING WRITING TO FOREIGN LANGUAGE (FL) STUDENTS IN EDUCATIONAL INSTITUTIONS - Ibragimova Dilafruz Shukhratovna; Karimova Dilzodaxon Lazizovna (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation: Teaching writing to foreign language (FL) students in educational institutions is a multifaceted endeavor that comes with its own set of challenges. However, by identifying these challenges and implementing effective solutions, educators can create an environment conducive to the development of strong writing skills among FL students. This article delves into some common problems faced by instructors and proposes viable solutions to enhance the teaching and learning process.